Statin therapy is associated with improved survival in patients with ventricular tachyarrhythmias - Rusnak, Jonas; Behnes, Michael; Schupp, Tobias; Lang, Siegfried; Reiser, Linda; Taton, Gabriel; Kern-Bollow, Armin; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; El-Battrawy, Ibrahim; et al. (Lipids in health and disease, 2019)
The study sought to assess the impact of statin therapy on survival in patients presenting with ventricular tachyarrhythmias.
Gesehen am 20.09.2019